New cryptanalysis of the authenticated cipher model JAMBU - Yu-dan TIAN; Yong-zhuang WEI (网络与信息安全学报)
Based on the characteristic of JAMBU,a forgery attack by using the principle,where the associated data can be transformed into the plaintext was proposed.It is shown that the attack requires a data complexity of about 2 n 2 chosen plaintext,and a time complexity of about 4× 2 n 2 encryptions.Compared with the previous attack,this attack is more favorable.